The Prosecutor's Pre-Prosecution And Prosecution In Accordance With The Criminal Procedure Code - Indra Utama Tanjung; Dinda Suciana Rambe; Chintya Jiliani; Gilang Septian Firjatullah (ISNU Sumatera Utara, 2026)
This article examines the legal construction and practical implementation of the prosecutor’s authority in pre-prosecution and prosecution under the Indonesian Criminal Procedure Code (KUHAP). The study departs from the normative ideal of an integrated criminal justice system that positions the prosecutor as dominus litis, responsible for controlling the flow of criminal cases from investigation to adjudication. Using a normative juridical method with a statute-based and conceptual approach, this research critically analyses the regulatory framework governing pre-prosecution and prosecution, as well as its application in practice. The findings indicate that although KUHAP formally grants prosecutors a strategic role in ensuring the completeness of case files and the legality of prosecutions, the existing regulatory design, particularly under the old KUHAP, tends to produce procedural formalism, weak coordination between investigators and prosecutors, and limited mechanisms of accountability. The article further argues that recent reforms introduced in the new KUHAP reflect a paradigm shift towards strengthening judicial control and due process safeguards, especially through the reconfiguration of pretrial mechanisms. However, these normative improvements still face structural and institutional challenges that may hinder their effectiveness. This study contributes to the development of criminal procedural law by highlighting the normative–practical gap in prosecutorial functions and offering a critical foundation for evaluating prosecutorial reform in Indonesia’s evolving criminal justice system.